2021
DOI: 10.1136/gutjnl-2021-325010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of COVID-19 after faecal microbiota transplantation

Abstract: Figure 1 Timeline of the procedures performed in patients with CDI, which coincidentally occurred during COVID-19 early stage infection. Created with BioRender.com. CDI, Clostridioides difficile infection; ESBL, extended-spectrum beta-lactamase, FMT, faecal microbiota transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 10 publications
(8 reference statements)
0
54
0
1
Order By: Relevance
“…Given the proposed role of gut microbiota in the abnormal activation of immune responses in the COVID-19, FMT can potentially be explored as a therapeutic strategy. A recent case report ( 85 ) described two patients with rapid resolution of COVID-19 after FMT was undertaken to treat concomitant C. difficile infection. However strong may be the hypothesis and surrounding speculations, FMT should not presently be recommended as a therapy against COVID-19 due to the scarcity of large-scale studies.…”
Section: Therapeutic Potential Of Gut Microbiome For Covid-19mentioning
confidence: 99%
“…Given the proposed role of gut microbiota in the abnormal activation of immune responses in the COVID-19, FMT can potentially be explored as a therapeutic strategy. A recent case report ( 85 ) described two patients with rapid resolution of COVID-19 after FMT was undertaken to treat concomitant C. difficile infection. However strong may be the hypothesis and surrounding speculations, FMT should not presently be recommended as a therapy against COVID-19 due to the scarcity of large-scale studies.…”
Section: Therapeutic Potential Of Gut Microbiome For Covid-19mentioning
confidence: 99%
“…In our recent study, we identified the genus Lachnospiraceae_NK4A136_group (phylum Firmicutes) as a food allergy-associated bacteria [41], and a recent study pointed to the existence of gut-associated bacteria, such as the family Lachnospiraceae in the lung microbiota of patients with ARDS [90]. Interestingly, recent studies introduced the therapeutic potential of fecal microbiota transplantation (FMT) for recurrent Clostridium difficile infection patients with COVID-19 [91,92]. In addition, a clinical trial (NCT04824222) to assess the impact of FMT on reducing the risk of disease progression as a supplement to standard COVID-19 treatment is ongoing [92].…”
Section: Hypothesis: Potential Impact Of Phototherapy With Full-spectrum Light On the Covid-19 Pandemicmentioning
confidence: 99%
“…Interestingly, recent studies introduced the therapeutic potential of fecal microbiota transplantation (FMT) for recurrent Clostridium difficile infection patients with COVID-19 [91,92]. In addition, a clinical trial (NCT04824222) to assess the impact of FMT on reducing the risk of disease progression as a supplement to standard COVID-19 treatment is ongoing [92]. On the other hand, Parabacteroides goldsteinii (phylum Bacteroidetes) was identified as a beneficial bacterial species enriched by phototherapy with full-spectrum light [41].…”
Section: Hypothesis: Potential Impact Of Phototherapy With Full-spectrum Light On the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to influence the gut microbiome more radically is faecal microbiota transplant (FMT). Two cases were reported, from an 80-and a 19-year-old man, who received an FMT to treat a Clostridioides difficile infection (CDI) [89]. Both had severe comorbidities.…”
Section: Targeting the Gut Microbiome As Adjunctive Therapy For Covid-19mentioning
confidence: 99%